2018
DOI: 10.3989/scimar.04679.21a
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and mortality of <em>Sciaena umbra</em> (Sciaenidae) in the Gulf of Tunis

Abstract: Summary:The growth and mortality of the brown meagre, Sciaena umbra from the Gulf of Tunis, were investigated using a sample of 276 specimens, ranging from 15.3 to 49.2 cm total length and from 43 to 1565 g total weight. Specimens were collected from artisanal fisheries between October 2008 and September 2011. Otoliths were extracted, thin cross-sections were realized and radii were measured. The log-linear morphometric relationships between total length-total weight and total length-otolith radius were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
14
1
Order By: Relevance
“…In this study, "b" value was calculated as 3.1909 and it was determined that growth was positive allometric (b>3). Few studies on the species reported that the growth were negative allometry (Karachle and Stergiou, 2008;Maci et al, 2009;Crec'hriou et al, 2013), while most of study reported to be positive allometric growth (Morey et al, 2003;Karakulak et al, 2006;La Mesa et al, 2008;Engin and Seyhan, 2009;Grau et al, 2009;Bilge et al, 2014;Chater et al, 2018). The "b" value may be different from one population to another of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, "b" value was calculated as 3.1909 and it was determined that growth was positive allometric (b>3). Few studies on the species reported that the growth were negative allometry (Karachle and Stergiou, 2008;Maci et al, 2009;Crec'hriou et al, 2013), while most of study reported to be positive allometric growth (Morey et al, 2003;Karakulak et al, 2006;La Mesa et al, 2008;Engin and Seyhan, 2009;Grau et al, 2009;Bilge et al, 2014;Chater et al, 2018). The "b" value may be different from one population to another of the same species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, maximum age, which was reported as “oddly missing” in the previous analysis, seems to have gained quite a few new records (n = 187; Table 1 ) in the last five years, for instance, for the species Sciaena umbra [ 52 ], Trachinotus ovatus [ 53 ] and Alepes djedaba [ 54 ]. Conversely, mortality records are still very few and exist for only a small percentage of the Mediterranean fish species ( Fig 1 , top row and Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum reported age for the meagre, Argyrosomus regius, in the Gulf of Cádiz (SW Iberian Peninsula) is 42 years (González-Quirós et al, 2011), while the brown meagre, Sciaena umbra, reached 31 years in the Gulf of Tunis (Chater et al, 2018). The dense calcium carbonate deposition of the large and very thick otoliths in Sciaenids reduces light transmission, making it almost impossible to distinguish hyaline and opaque zones (Arneri et al, 1998;Chater et al, 2018). According to Arneri et al (1998), growth increments in otoliths of these taxa are more readable in cross-sections.…”
Section: Opportunities For Fish Growth Chronology Constructionmentioning
confidence: 99%